2022
DOI: 10.3390/foods11020196
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Plastein Reaction of Casein Hydrolysates in the Presence of Exogenous Amino Acids on Their Anti-Inflammatory Effect in the Lipopolysaccharide-Stimulated Macrophages

Abstract: In this study, papain-generated casein hydrolysates (CH) with a degree of hydrolysis of 13.7% were subjected to a papain-mediated plastein reaction in the absence or presence of one of the exogenous amino acids—Gly, Pro, and Hyp—to prepare four plastein modifiers, or mixed with one of three amino acids to prepare three mixtures. The assay results confirmed that the reaction reduced free NH2 for the modifiers and caused amino acid incorporation and peptide condensation. When RAW264.7 macrophages were exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…(2012), who assessed the anti‐inflammatory effects of Oyaksung which was fermented with Lactobacillus on RAW 264.7 cells. Similarly, Shi and Zhao (2022) had reported the anti‐inflammatory property of casein hydrolysates using RAW 264.7 cells against LPS‐induced inflammation. Hence, this outcome indicated its profound role of anti‐inflammatory response in the development and progression of inflammatory conditions.…”
Section: Resultsmentioning
confidence: 91%
“…(2012), who assessed the anti‐inflammatory effects of Oyaksung which was fermented with Lactobacillus on RAW 264.7 cells. Similarly, Shi and Zhao (2022) had reported the anti‐inflammatory property of casein hydrolysates using RAW 264.7 cells against LPS‐induced inflammation. Hence, this outcome indicated its profound role of anti‐inflammatory response in the development and progression of inflammatory conditions.…”
Section: Resultsmentioning
confidence: 91%
“…In LPS-treated IEC-6, bovine lactoferrin also had an anti-inflammatory effect by reducing the secretion of IL-6, TNF-α, and IL-1β, as well as suppressing MAPK activation and the nuclear translocation of NF-κB [ 57 ]. When casein hydrolysates were modified by plastein reactions in the presence of exogenous amino acids, the obtained modifiers demonstrated greater anti-inflammatory activity against LPS-induced macrophage inflammation, mostly by controlling IL-6 and TNF-α production and preventing the activation of the NF-κB signaling pathway [ 58 ]. However, certain protein by-products generated during the Maillard process seem to have an ability to encourage the undesirable cellular inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation occur concomitantly and act as key players in many disease conditions including COVID‐19 (Delgado‐Roche & Mesta, 2020 ). So far a number of scientific studies have reported the antioxidant (free radical scavenging and metal chelating activities) and anti‐inflammatory activities of CN‐derived peptides (Altmann et al, 2016 ; Bamdad et al, 2017 ; Chen et al, 2022 ; Li, Cheng, et al, 2017 ; Mukhopadhya et al, 2015 ; Oh et al, 2017 ; Shi & Zhao, 2022 ; Yoo et al, 2021 ). Mao et al ( 2011 ) prepared yak milk CN hydrolyzates with enzyme alcalase and observed their significant free radical scavenging activities in terms of 2,2‐diphenylpicrylhydrazyl, superoxide, and hydrogen peroxide (H 2 O 2 ).…”
Section: Milk Proteinsmentioning
confidence: 99%